Bioethical issues in biomedical research involving Chilean indigenous populations - Fajreldin, Valentina (Acta Bioethica, 2010)
In Chile there are diverse governmental and social instances to work with the health of indigenous populations and there has been fruitful outcome; nevertheless, some health care access and coverage inequities persist in these populations. Biomedical research effort carried out with aboriginal populations in our country is hidden, what threatens many times the genetic patrimony of these communities. This text would like to build a bridge between medical anthropology, public health and bioethics. Considering the state of the art in the issue, we propose some elemental work axis on the issue, which serves as basis to get a place within bioethics endeavors at Chile, with the goal of contributing to a process both necessary and urgent: the formulation of a public health culturally aware.